Crimmigration in the Age of COVID-19 - Koulish, Robert (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In 2020-2022, much of the world was at risk for catching COVID-19. This reprint, "Crimmigration in the Age of COVID-19," contributes to understanding immigration during the pandemic. It engages a cross-national and interdisciplinary case-study approach to show how countries carved out exceptions to public health protocols for migrants. In the immigration context a variety of governments weaponized public health protocols to criminalize and exclude migrants. The Trump Administration sadistically misplayed the pandemic at almost every turn. Trump came to power on the backs of migrants, referring to them as murderers and rapists. The intersection of Trump's COVID-19 and migration policies carved out space for the exceptional dehumanization of migrants in 2020-21. This reprint documents the weaponization of public through crimmigration. Crimmigration is the criminalization of migration and migrants via state-of-the-art surveillance and militarized technologies. During the worst of COVID-19, crimmigration strategies--mandatory detention and harsh exclusions- exacerbated the risk of transmission among migrants. Policies not migrants were to blame here. The ostensibly public health related Title42 actually pushed migrants, already at great risk, into unregulated shantytowns controlled by Mexican drug cartels. Additionally, migrants contended with detention facilities, medium security prisons, that functioned as Petrie dishes for the disease. We hope this reprint contributes to understanding the intersection of public health and crimmigration, and border penologies during these exceptional times.